Desalination of saline water and wastewater using graphene oxide mixed matrix membranes through pervaporation method - Mahsa Torkian; Akbar Malekpour (Desalination and Water Treatment)
Mixed matrix membranes composed of polyvinyl alcohol (PVA) and graphene oxide (GO) were synthesized using the blending and casting method. The properties of the prepared membranes were characterized using X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), Fourier transform infrared spectroscopy (FTIR), tensile strength testing, and contact angle measurement. The membranes’ ability to desalinate saline solutions was investigated using the pervaporation method, focusing on two key parameters: flux and rejection. The effects of GO loading, temperature, feed solution pH and membrane thickness were studied, explained and compared with neat PVA membranes and other reported works. The results indicated that incorporating GO into PVA enhances the membrane’s strength and makes it possible to use thinner membrane and finally it causes a significantly increase in flux. Desalting of different solutions containing Na+, Mg2+, Ca2+, Fe3+ and Al3+ ions, alone or together often showed the rejection values more than 99 %. Among them the best performance was achieved for a feed containing 1000 mg/L of Fe (III) at a temperature of 50°C, with an outstanding permeability value of 38.47 kg.m-²·h−1 and a rejection rate of 99.99 %. Overall, the results demonstrate these composite membranes are highly efficient and economical for water and wastewater treatment.